2013
DOI: 10.3389/fpsyt.2013.00001
|View full text |Cite
|
Sign up to set email alerts
|

Proof of Concept Trial of Dronabinol in Obstructive Sleep Apnea

Abstract: Study Objective: Animal data suggest that Δ9-TetraHydroCannabinol (Δ9THC) stabilizes autonomic output during sleep, reduces spontaneous sleep-disordered breathing, and blocks serotonin-induced exacerbation of sleep apnea. On this basis, we examined the safety, tolerability, and efficacy of dronabinol (Δ9THC), an exogenous Cannabinoid type 1 and type 2 (CB1 and CB2) receptor agonist in patients with Obstructive Sleep Apnea (OSA). Design and Setting: Proof of concept; single-center dose-escalation study of drona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
195
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 156 publications
(211 citation statements)
references
References 16 publications
(20 reference statements)
11
195
2
3
Order By: Relevance
“…Conversely, we found that subjects reported decreased daytime sleepiness while taking oral dronabinol. 3 Although not conclusive, these data are consistent with the possibility that the shift toward lower sleep EEG frequencies, and in particular the observed increase of relative theta power, reflects a direct CNS effect of dronabinol, and therefore a potential biomarker of its sedating properties.…”
supporting
confidence: 49%
See 4 more Smart Citations
“…Conversely, we found that subjects reported decreased daytime sleepiness while taking oral dronabinol. 3 Although not conclusive, these data are consistent with the possibility that the shift toward lower sleep EEG frequencies, and in particular the observed increase of relative theta power, reflects a direct CNS effect of dronabinol, and therefore a potential biomarker of its sedating properties.…”
supporting
confidence: 49%
“…We previously demonstrated that oral dronabinol decreased apnea hypopnea index (AHI) in subjects with OSA. 3 Interestingly, although overall sleep stage percentages did not change with treatment, daytime sleepiness decreased signifi cantly. Here, we hypothesized that simple sleep stage distributions may be insensitive to important aspects of sleep architecture contributing to improved alertness with dronabinol treatment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations